Preparation and characterization of a novel cuprous complex. Issue 4 (16th November 2020) - Zhang, Ding-Wa; Luo, Hui; Chen, Wen-Tong
Abstract : Cu4 Cl4 (2, 2′-bpy)2 (1 ) (bpy = bipyridine) was obtained and characterized. It crystallizes in the triclinic system P (−1) space group. It is a discrete motif. Cu1 is bound by two nitrogen (N) atoms and two chloride (Cl − ) ions, generating a tetrahedron. Cu2 is bound by two chloride ions to generate a line. A Cu4 Cl4 moiety is generated by four chloride and four cuprous (Cu + ) ions and connects to two 2, 2′-bpy molecules to generate Cu4 Cl4 (2, 2′-bpy)2 . It has a blue photoluminescence emission, which can be attributed to ligand-to-ligand charge transfer and metal-to-ligand charge transfer. Time-dependent density functional theory calculations were conducted with the Gaussian03 program. The X-ray diffraction software is CrystalClear.